Pendekatan Restorative Justice Dalam Penyelesaian Perkara Tindak Pidana Narkotika Pada Tahapan Penyidikan - Jesylia Hillary Lawalata; Juanrico Alfaromona Sumarezs Titahelu; Julianus Edwin Latupeirissa (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: The handling of narcotics abuse is carried out by two methods, namely prevention without punishment through mandatory reporting of addicts and implementation of rehabilitation law enforcement with a restorative justice approach. Restorative Justice, is a model of a criminal case settlement approach where all parties with an interest in the case meet together to resolve fairly by emphasizing returning to its original state and not retaliation.Purposes of the Research: This study aims to analyze and discuss the mechanisms and procedures for resolving narcotics crime cases at the investigation stage with the Restorative Justice approach at the investigation stage and to analyze and discuss the investigator's considerations in resolving narcotics crime cases through restorative justice at the investigation stage. Methods of the Research: The research method used is a normative juridical research type. The problem approach used is the statutory approach, concept analysis approach, and case approach. The legal materials used are primary legal materials and secondary legal materials. Procedures and Collection of Legal Materials through literature study and Processing and Analysis of legal materials are then analyzed by means of description using qualitative methods.Results of the Research: The results of the study show that the mechanisms and procedures for resolving narcotics crime cases with a restorative justice approach at the investigation stage are as follows: making administrative investigations (initial interrogation, celebrating communication tools, case titles, making police reports, investigation warrants, minutes of witness examinations). , urine test), the suspect submits a letter of application to the Kapolda/Kapolres, the investigator makes the administration of the investigation (request for assessment, determination of the status of evidence, determination of approval for confiscation, Minutes of Examination of the Suspect), implementation of assessment, coordination with Balai POM, results of assessment and recommendation of Kapolda / Police Chief, case title (Warrant for Termination of Investigation). Investigators' considerations in resolving narcotics crime cases with a restorative justice approach at the investigation stage are: the suspect is a victim of drug abuse, the urine result is positive, the suspect is not involved in the network, has An assessment has been carried out and the suspect is willing to cooperate with investigators in eradicating narcotics trafficking.